Dental care necessity at productive age in Cilayung Village, Jatinangor Districts, Sumedang Regency - Atlantika, Granidya Rosa; Suwargiani, Anne Agustina; Susilawati, Sri (Universitas Padjadjaran, 2017)
Introduction: The need of dental care is defined as a collection of dental and oral treatment in which according to dental personnel should be obtained by a certain period in order to achieve good dental health status. According to WHO, the productive age is the age group between 35-44 and is considered as the standard age for checking the adult oral health condition. The objective of this research was to obtain the necessity of oral health data at productive age in Cilayung village. Method: The research method was descriptive with cluster sampling technique. Samples of 80 respondents were obtained by pathfinder surveys technique. The necessity of dental care was assessed using WHO oral health surveys and the dental condition of respondents were checked using mouth glass. Result: The results shows that the highest number of caries prevention is as many as 80 people (100%) and the need for one surface treatment as many as 75 people (93.75%). Conclusion: The research concluded that the people in Cilayung village is in high need of caries and surface treatment.